Behavioural Asset Pricing: A Review - Nanayakkara, N. S.; Nimal, P. D.; Weerakoon, Y. K. (International Journal of Economics and Financial Issues, 2019)
Neoclassical asset pricing is built on the premise investors are rational and there are unlimited arbitrage opportunities. Behavioural implications of irrational investors led to the development of the counter paradigm, behavioural asset pricing. This study systematically reviews the origin and evolution of behavioural asset pricing distinct to neoclassical asset pricing. It addresses the two pillars of behavioural asset pricing where; investors are not always rational and there are limits to arbitrage. The study captures investor irrationality in two perspectives; investors’ beliefs and their preferences. It reviews psychological biases and heuristics adopted from experimental psychology to behavioural asset pricing in explaining beliefs and preferences of irrational investors. Furthermore, it lists key biases and heuristics recognised in behavioural asset pricing literature. It discusses theoretical behavioural asset pricing models that try to explain variation of stock returns through specific biases of investor psychology. Lastly, the study reviews aggregate investor sentiment studies that try to capture mass psychology of investors in financial markets. The significance of this study is that it attempts to develop a holistic view of the foundation and evolution of behavioural asset pricing. Keywords: Asset pricing, behavioural finance, irrational investor, arbitrage, biases, heuristics JEL Classifications: D81, D91, G12 DOI: https://doi.org/10.32479/ijefi.8190